MC903으로 유도하는 아토피피부염 생쥐 동물 모델 최적화 : 유발 기간 단축 및 부작용 감소를 중심으로 - 김소연(Soyeon Kim); 류지효(Ji Hyo Lyu); 김형우(Hyungwoo Kim) (동의생리병리학회지, 2023)
This study was designed to establish an atopic dermatitis (AD) model using MC903 and was conducted to find out the optimal challenge concentration that can cause dermatitis symptoms enough to be experimentally verified while reducing adverse effects such as weight loss. MC903 was treated at concentrations of 2, 3, and 4 nmol/day, and evaluation of skin surface symptoms, water contents, histopathological changes, body weight changes, and spleen/body weight ratio was conducted. In addition, the expression level of thymic stromal lymphopoietin (TSLP) was also observed. In our results, MC903 induced AD skin lesions such as erythema, scab and fissure and lowered skin moisture level significantly. In addition, water holding capacities in the 3 or 4 nmol groups were diminished significantly compared to that in the control group. On the other hand, 4 nmol treatment induced a weight loss of up to 20% compared to control group. Finally, a higher level of TSLP expression was observed in the 3 nmol group than in the 2 nmol group or the 4 nmol group. Taken together, we propose a total 14-day protocol consisting of 3 days of sensitization (2 nmol/day) and 6 days of challenge (3 nmol/day).